Bioactive lipids and allelopathic potential of the invasive plant Heracleum sosnowskyi: insights into its fatty acid composition, antimicrobial and cytotoxic effects - Borska, Eva; Kviesis, Jorens; Ramata-Stunda, Anna; Nikolajeva, Vizma; Ansone-Bertina, Linda; Boroduskis, Martins; Klavins, Maris (Frontiers in Pharmacology, 2025)
Sosnowsky’s hogweed (Heracleum sosnowskyi Manden) is one of the most dangerous invasive plant, notorious with presence of toxic substances. At the same time H. sosnowskyi phytochemistry from perspective of applications in pharmacology, especially lipids have not been much studied. This study aims to analyse lipids of H. sosnowskyi, especially fatty acids, their composition, metabolism patterns and biological activity. Extraction possibilities of lipids from different parts of H. sosnowskyi have been studied and besides traditional solvents, so called green solvents can be used. In lipid extracts various positional and geometric isomers of fatty acids have been found and their concentrations and profiles differ amongst plant parts. Multifactor statistical analysis demonstrates the contribution of the metabolism of fatty acids in different parts of a plant. H. sosnowskyi lipid extracts demonstrate high antimicrobial activity and cytotoxic activity against cancer cell lines and so plant biomass after eradication can be used to obtain substances with high application potential in the bio-pharma industry.